Meningkatkan Kemampuan Penjumlahan Melalui Media Stick Angka pada Anak Disabilitas Intelektual Ringan di SLB YPAC Sumatera Barat (Indo-MathEdu Intellectuals Journal, 2025)
This research is motivated by the issue of a child with mild intellectual disabilities who is not yet capable of performing addition with results up to 20, even though the student has already reached the 8th grade in a special education school. Based on the identified problems, the student needs to be provided with learning media to enhance their addition skills as well as to increase motivation in learning. Number Stick Media is one type of learning media that can be used to assist children in learning mathematics, specifically addition. The type of research used is quantitative with an experimental approach in the form of Single Subject Research (SSR) using an A-B design. The subject of this research is children with mild intellectual disabilities in the eighth grade at SLB YPAC West Sumatra. The data collection techniques used in this study involved interviews and tests. The data analysis technique used is graphical visual analysis. The results of the study indicate that in the baseline condition (A), a percentage result of 35%, 35%, and 35% was obtained. In the intervention condition (B), results of 65%, 80%, 85%, 85%, 90%, 90%, and 90% were obtained. Based on the data analysis that has been conducted, it was found that the use of stick number media can improve the ability to add lateral series with results up to 20 for children with mild intellectual disabilities at SLB YPAC West Sumatra.